2019
DOI: 10.21037/qims.2019.08.10
|View full text |Cite
|
Sign up to set email alerts
|

MR image reconstruction using deep learning: evaluation of network structure and loss functions

Abstract: Background: To review and evaluate approaches to convolutional neural network (CNN) reconstruction for accelerated cardiac MR imaging in the real clinical context. Methods: Two CNN architectures, Unet and residual network (Resnet) were evaluated using quantitative and qualitative assessment by radiologist. Four different loss functions were also considered: pixel-wise (L1 and L2), patch-wise structural dissimilarity (Dssim) and feature-wise (perceptual loss). The networks were evaluated using retrospectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 25 publications
3
72
2
Order By: Relevance
“…Although DeepBLESS achieved almost instantaneous T 1 /T 2 map reconstruction for the radial T 1 ‐T 2 mapping sequence, the compressed‐sensing reconstruction took approximately 3 minutes, a limitation for using the radial T 1 ‐T 2 sequence for simultaneous myocardial T 1 and T 2 mapping. Recent studies have shown that deep learning can be applied to replace compressed sensing, to reduce reconstruction time 35‐37 . These techniques may be combined with our proposed T 1 calculation technique to further reduce total imaging time and enable online use of the radial T 1 ‐T 2 mapping technique.…”
Section: Discussionmentioning
confidence: 99%
“…Although DeepBLESS achieved almost instantaneous T 1 /T 2 map reconstruction for the radial T 1 ‐T 2 mapping sequence, the compressed‐sensing reconstruction took approximately 3 minutes, a limitation for using the radial T 1 ‐T 2 sequence for simultaneous myocardial T 1 and T 2 mapping. Recent studies have shown that deep learning can be applied to replace compressed sensing, to reduce reconstruction time 35‐37 . These techniques may be combined with our proposed T 1 calculation technique to further reduce total imaging time and enable online use of the radial T 1 ‐T 2 mapping technique.…”
Section: Discussionmentioning
confidence: 99%
“…B (from top to bottom), sample of the original motion-free image, the synthesized respiratory motion-corrupted image, and the error map between them mentioned groups, which pairs had statistically significant difference? To answer these questions, Friedman's two-way analysis 51,52 and nonparametric paired comparison tests were applied. Significance level for all statistical tests was assumed at α = 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters that we chose to build the neural networks should stay consistent throughout our trials. A loss function is required in many neural networks and can lead to performance increases/decreases depending on the type of problem that is being tackled [24]. Figure 5A).…”
Section: Constructed Artificial Neural Network (Anns) Predict Gbm Sumentioning
confidence: 99%